VALUE INCREASING OF REJECT COAL WITH BIOMASS ADDING AS BIO-COAL BRIQUETTE - Dyah Marganingrum; Lenny Marilyn Estiaty (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2020)
Aim: This paper aims to explain the added value increasing method of reject coal which has not utilized by the company. Methodology and Results: The method to increase added value in this study used the agglomeration process of briquettes form that changing composition by adding biomass. The biomass functions to minimize bottom ash produced from burning briquettes so that the briquettes burn entirely. Stages processes in this study consist of characterization, briquetting, physical test, and chemical test. Based on the analysis, reject coal still has a high calorific value of 5,929 cal/gr. Shapes and sizes that were not following needs of coal market or consumer due to reject coal to be a waste. Briquettes have been successfully produced and meet specification requirements based on applicable regulations in Indonesia. Besides physical properties, the briquette meet density requirements which are greater than or equal to 1 gr/cm3 and shatter index value is less than 0.5%. The gas emission test shows below threshold, which is CO 0-30 ppm, H2S 0-3.6 ppm, and NOx is not detected. After evaluation, it showed that by adding 30% biomass, ignition time could be decreased and remaining unburned briquettes or bottom ash was reduced as much as 68.68%. Conclusion, significance and impact study: The bio-coal briquettes is a strategic solution to environmental problems and alternative energy sources that are environmentally friendly, because CO and H2S emissions are still below the threshold, even for NOx not detected. Making Bio-coal briquettes as a solution to the utilization of reject coal mining waste to be used as an alternative energy source has been successfully carried out.